RETRACTED: Surgical Treatments for Canine Anterior Cruciate Ligament Rupture: Assessing Functional Recovery Through Multibody Comparative Analysis - Putame, Giovanni; Terzini, Mara; Bignardi, Cristina; Beale, Brian; Hulse, Don; Zanetti, Elisabetta; Audenino, Alberto (Frontiers in Bioengineering and Biotechnology, 2019)
Anterior cruciate ligament (ACL) deficiency is responsible for serious degenerative stifle injuries. Although tibial plateau levelling osteotomy (TPLO) is a common method in treating ACL deficiency, the best surgical treatment based on osteotomy has not been clearly identified yet. The leveling osteotomy based on the center of rotation of angulation (CBLO) represents a possible alternative to TPLO. The aim of this study is to compare TPLO and CBLO effectiveness in treating ACL rupture. First, a computational multibody model of a physiological stifle was created using three-dimensional standardized canine femur, tibia, fibula and patella. Contacts between bones were properly modelled and ligaments were represented by vector forces connecting origin and insertion points. The lengths of the ligaments at rest were optimized using the drawer test. The ACL-deficient model was obtained by deactivating the ACL related forces in the optimized physiological one. Then, TPLO and CBLO treatments were virtually performed on the pathological stifle. Finally, the drawer test and the weight-bearing squat movement were performed to compare the treatments effectiveness in terms of tibial anteroposterior translation, patellar ligament force, intra-articular compressive force and quadriceps force. Results from the drawer test showed that ACL-deficiency causes an increment of the anterior tibial translation. During the squat simulation, CBLO leads to an increment of the intra-articular compressive force at 90° of flexion, compared to the physiological model. This same increment is limited when TPLO is performed. Moreover, TPLO generates lower forces in patellar ligament and quadriceps muscle, compared to CBLO. However, CBLO produces a lower intra-articular compressive force for the physiological walking range of flexion, compared to TPLO. Overall, no significant differences between CBLO and TPLO were recorded for the clinical drawer test, while squat simulations have demonstrated that both treatments lead to an increment of all considered forces. The higher patellar ligament forces produced by the CBLO cause higher ligament stresses which may lead to ligament thickening or desmitis. As known, surgery for ACL-deficiency is performed on pathologic stifles characterized by degenerated cartilage. Therefore, the higher intra-articular compressive force during walking, as resulting from TPLO, should be a reason of concern for this technique.